Genetic Expression Profile of Vitamin D Metabolizing Enzymes in the First Trimester - Ekström, L.; Storbjörk, L.; Björkhem-Bergman, L. (Hormone and Metabolic Research, 2016)
The aim of this study was to map the genetic expression of the vitamin D metabolizing enzymes CYP27A, CYP27B1, CYP2R1, and CYP24A1 in the first trimester in different human fetal tissues. In addition, the gene expression was correlated with fetal age, season, and presence of single nucleotide polymorphisms (SNPs) in the genes encoding CYP27A1 (rs4674344), CYP2R1 (rs2060793), and CYP24A1 (rs6013897). Fetal samples from livers (n=60), kidneys (n=43), lungs (n=37), and intestines (n=14) were analyzed by quantitative PCR. In addition, the expression of the enzymes was also analyzed in adult livers (n=20). The highest expression of CYP2R1 and CYP24A1 was found in fetal kidney and lung. CYP27A1 was expressed at the highest levels in the liver and kidney and CYP27B1 had the highest levels in the kidney. The expression of fetal hepatic CYP2R1 and CYP27A1 was increased during summertime. Carriers of the G-allele of the rs2060793 SNP in the CYP2R1 gene, a genotype previously associated with rickets, had lower levels of CYP2R1 mRNA.In conclusion, this study suggest that the kidneys rather than the liver, may be of importance for fetal vitamin D metabolism, even for the 25-hydroxylation, during the first trimester. The results also suggest that the lungs and intestines are important for vitamin D metabolism in the fetus. Finally, GG- carriers of the rs2060793 SNP had significantly lower CYP2R1 expression and might be at risk for 25-hydroxyvitamin D deficiency.
Keywords: fetal metabolism; vitamin D metabolism; genetic polymorphism; CYP27B1; CYP2R1; CYP24A1